Biodiversity of Echinodermata in Marsegu Island - Bijaya Latupono; Fredy Leiwakabessy; Dominggus Rumahlatu (Sriwijaya Journal of Environment, 2017)
Echinoderms are key species that govern the structure and balance of communities and influence the sustainability of other organisms in different types of ecosystems in sea water. This research aimed at examining the biodiversity of echinoderms, and environmental physical-chemical factors that affect the diversity of echinoderms in coastal waters of Marsegu Island. The data were collected with direct observation and all research variables were recorded. The data collection of echinodermata type was done on each plot in the middle intertidal zone and the lower intertidal zone. The results of this research found that the population of echinoderms in coastal water of Marsegu Island was composed of 4 classes, namely Ophiuroidea, Asteroidea, Echinoidea and Holothuriodea. The most common type found was Asteroidea which consisted of 3 families, 4 genera and 4 species. The results of observation showed there was a difference in echinoderm species found in the middle intertidal zone and the lower intertidal zone. The number of echinoderms species found in the middle intertidal zone was 8 species, while in the lower intertidal zone was 10 species, and there were some species that were not found in the middle intertidal zone, but they were found in the lower intertidal zone, namely Ophiopholis aculeafa, Linckia laevagata and Protoreaster nodusus. The Synapta maculata species was found in the lower intertidal zone, but it was not found in the midle intertidal zone. About 52% variation in echinoderms diversity can be explained by the regression equation model, while the remaining 48% was the influence of other factors that could not be explained by the regression equation model.